(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Many, individualsexperience various types of heightened awareness and may seem overly sensitive.These sensitivities may be to physical senses such as sight, sound, smell,movement and touch. For example, they may be extremely uncomfortable when theyhave a wrinkle in their sock, or unable to concentrate because of the sound ofa clock ticking on the other side of the room. Sensitivities of the , are oftento mental and emotional over-awareness. For example, picking up on the ofsomeone close to them, having extreme sensitivity to their own internalemotions, and taking in external information at a significantly higher ratethan those around them.